Experimental Investigations of Traveling Wire Electro-Chemical Spark Machining (TW-ECSM) of Borosilicate Glass - Bhuyan, Basanta Kumar; Yadava, Vinod (Asian Review of Mechanical Engineering, 2012)
Traveling Wire Electro-Chemical Spark Machining (TW-ECSM) is an innovative hybrid machining process, combining the features of the Electro Chemical Machining (ECM) and Wire-Electro Discharge Machining (WEDM). It is more suitable for machining of electrically non-conductive engineering materials. Conventional machining methods and some unconventional machining methods cannot be effectively applied for machining of borosilicate glass due to the resulting problems of air borne dust, tool wear and thermal damage. In this paper an inhouse TW-ECSM setup has been designed and fabricated successfully and employed for experimentation. The results about the feasibility of the process and its performance during machining of borosilicate glass have been illustrated. Borosilicate glass, which is frequently used as a material for fabrication of micro structures, was used as a workpiece. Experiments were carried out to investigate the effects of specimen thickness along with different type of wires on material removal rate (MRR). For same set of input parameters, material removal rate is found to decrease initially but after achieving certain value, it begins to increase with increase in specimen thickness.